Rapid taqman-based quantification of chlorophyll d-containing cyanobacteria in the genus acaryochloris - Behrendt, Lars (2015)
Reports of the chlorophyll (Chl) d-containing cyanobacterium Acaryochloris have accumulated since its initial discovery in 1996. The majority of this evidence is based on amplification of the gene coding for the 16S rRNA, and due to the wide geographical distribution of these sequences, a global distribution of Acaryochloris species was suggested. Here, we present a rapid, reliable, and cost-effective TaqMan-based quantitative PCR (qPCR) assay that was developed for the specific detection of Acaryochloris species in complex environmental samples. The TaqMan probe showed detection limits of ∼10 16S rRNA gene copy numbers based on standard curves consisting of plasmid inserts. DNA from five Acaryochloris strains, i.e., MBIC11017, CCMEE5410, HICR111A, CRS, and Awaji-1, exhibited amplification efficiencies of >94% when tested in the TaqMan assay. When used on complex natural communities, the TaqMan assay detected the presence of Acaryochloris species in four out of eight samples of crustose coralline algae (CCA), collected from temperate and tropical regions. In three out of these TaqMan-positive samples, the presence of Chl d was confirmed via high-performance liquid chromatography (HPLC), and corresponding cell estimates of Acaryochloris species amounted to 7.6 × 101 to 3.0 × 103 per mg of CCA. These numbers indicate a substantial contribution of Chl d-containing cyanobacteria to primary productivity in endolithic niches. The new TaqMan assay allows quick and easy screening of environmental samples for the presence of Acaryochloris species and is an important tool to further resolve the global distribution and significance of this unique oxyphototroph.